2015
DOI: 10.1016/j.virusres.2015.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Bovine viral diarrhea virus type 2 in vivo infection modulates TLR4 responsiveness in differentiated myeloid cells which is associated with decreased MyD88 expression

Abstract: Symptoms of bovine viral diarrhea virus (BVDV) infection range from subclinical to severe, depending on strain virulence. Several in vitro studies showed BVDV infection impaired leukocyte function. Fewer studies have examined the effects of in vivo BVDV infection on monocyte/macrophage function, especially with strains of differing virulence. We characterized cytokine production by bovine myeloid cells isolated early or late in high (HV) or low virulence (LV) BVDV2 infection. Given BVDV infection may enhance s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…Peripheral blood mononuclear cells were isolated and red blood cells (RBC) lysed with buffered ammonium chloride salt solution [ 21 ]. After RBC lysis, cells were washed with sterile phosphate-buffered saline (PBS).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Peripheral blood mononuclear cells were isolated and red blood cells (RBC) lysed with buffered ammonium chloride salt solution [ 21 ]. After RBC lysis, cells were washed with sterile phosphate-buffered saline (PBS).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were resuspended in complete RPMI 1640 (cRPMI) containing 10% fetal bovine serum (tested commercially and in house to be free of BVDV and antibodies against BVDV), 2 mM L-glutamine, 1% antibiotic–antimycotic solution, and gentamicin sulfate (Life Technologies—Gibco, Carlsbad, CA). Monocytes were isolated by plastic adherence for 2 h as previously described [ 21 ]. Ice-cold PBS was added to the plate and adherent cells were removed with a cell scraper.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Histopathological observations showed lymphoid depletion and shedding of the villi of the small intestine. Many studies have reported that animals infected with non BVDV show leukocyte depletion, failure to induce the production of type I interferon α/β, immune suppression, and often secondary infections [32][33][34][35] .…”
Section: Discussionmentioning
confidence: 99%
“…33 Similarly, in vivo BVDV infection also modulates the capacity of monocytes and macrophages to respond via TLR4. 34 Like BVDV, several other viruses have an impact on APC activation and function. PIV infection suppresses macrophage phagocytosis and inhibits oxidative burst.…”
Section: Antigen-presenting Cells: Monocytes Macrophages and Dendritmentioning
confidence: 99%